Application of Electric Fields to Reduce Microorganism Contamination for Animal-Based Products - Yudhistira, Bara; Husnayain, Naila; Punthi, Fuangfah (Jurnal Teknologi Hasil Pertanian, 2023)
Non-thermal preservation has become popular recently for the preservation of animal-based products. One of the non-thermal preservation methods is the electric field (EF) treatment of food, which can suppress enzyme and microorganism activity. The EF treatment itself consists of various types, including pulsed electric fields (PEF), high-voltage electric fields (HVEF), and alternating capacitive electric fields (ACEF and DCEF). This review discusses the EF treatment effects, especially PEF, on animal-based product preservation, including mechanisms, advantages and disadvantages, PEF application, and its preservation effect. PEF has the potential to be widely applied in food processing. The application of PEF (Pulsed Electric Field) can be applied to animal-based products and has an effect on population age and microbial production. This is because PEF can inhibit microbial activity and growth depending on process parameters, including pulse waveform, treatment time, pulse width, pulse frequency, EF strength, and food matrix type. PEF can be used for pretreatment of liquefaction processes.